Virtual Jumu’ah Prayer: Debates, Challenges, and Scholar Perspectives Amidst The COVID-19 Pandemic - Achmad, Adang Darmawan; Qotadah, Hudzaifah Achmad (Journal of Modern Islamic Studies and Civilization, 2024)
Jumu’ah, regarded as the pinnacle of the weekly Islamic worship, mandates ritual purification, donning immaculate attire, and congregating at the mosque for Friday Prayer. However, the onset of the COVID-19 pandemic has necessitated adaptations in religious practices, compelling Muslims to pivot towards virtual modes of worship in compliance with directives issued by governmental and health authorities aimed at mitigating the transmission of the coronavirus. The transition to virtual or online prayer has sparked considerable theological discourse and scrutiny in light of the pandemic's challenges. Consequently, this research aims to rigorously examine the doctrinal perspectives on virtual Friday prayer. Employing a comprehensive qualitative methodology, this study undertakes a detailed descriptive analysis. Findings underscore ongoing theological debates among Muslim scholars worldwide, including in Indonesia, where divergent viewpoints exist regarding the permissibility of participating in Jumu’ah prayer remotely via broadcast or live streaming under any theological school (madhhab). Critics argue against virtual congregational prayer due to logistical challenges posed by physical distancing, asserting that the spatial and communal integrity essential to Islamic worship may be compromised. Conversely, proponents advocate for a pragmatic approach, invoking the principle of maslahat (public interest) to safeguard the continuity of Friday prayers amidst unprecedented circumstances. In conclusion, this study contributes to the scholarly discourse on contemporary Islamic jurisprudence by elucidating the multifaceted debates surrounding virtual Jumu’ah prayer during the COVID-19 pandemic, reflecting diverse interpretations and applications of Islamic law in response to evolving global challenges.